2011 lAAF World Championships in Daegu: blood tests for all athletes in the framework of the Athlete Biological Passport. (July 2012) - Robinson, Neil; Dollé, Gabriel; Garnier, Pierre-Yves; Saugy, Martial
The 2011 International Association of Athletics Federation (IAAF) World Championships took place in Daegu, Korea. For the first time, all athletes were blood tested prior to the competition in order to give a clear signal to the world athletic community of the wish to enter into the era of the Athlete Biological Passport and fight against doping in their sport. The hematological parameters were measured on site. Thus, a mobile-accredited laboratory for blood testing was created in Daegu. Two serum tubes were collected for clinical chemistry and hormonal analyses in order to build the bases of the endocrine and the androgen (steroid) modules of the Athlete Biological Passport in blood. This paper describes some of the main challenges the project faced with regard to the large number of athletes, competing in different disciplines, and the logistic problems that had to be solved for smart implementation of one of the most complex operations organized in the last decade in the fight against doping.